Model Manajemen Usaha dan Hubungannya dengan Kinerja UKM (Studi Kasus pada UKM Sembung Batik Kulonprogo Jogyakarta) - H Fikriah; Muhaimin; Muhammad Arya Dirgantara (Jurnal EMT KITA, 2023)
Indonesian SMEs play an important role in employment and contribution to GDP. However, complex issues still hamper the progress and rise of SMEs. This research aims to explore the causes of these problems by focusing on management models in SMEs. The study uses qualitative methods through interviews, observations, and documentation. The research subject was UKM "Sembung Batik" in Kronprogo, Yogyakarta. We manufacture batik fabrics with letters and prints and develop fashion products with batik motifs. It is hoped that the results of this study will explain the relationship between the operating model implemented by Sembung Batik UKM and its operating performance. In this way, new management solutions and models can be developed that are more effective and efficient for improving the performance of small businesses. This study uses SWOT analysis as an indicator of performance evaluation and considers aspects of corporate governance such as manufacturing, marketing, finance, and human resources. The findings show that Sembung Batik UKM has significant development potential with increased assets, turnover and net profit. However, traditional management models with manual financial and production controls are still an obstacle. Low technology utilization in the areas of production, marketing, human resources, and accounting information systems also means that small businesses are not performing optimally. Efforts to increase income are possible through product diversification, hiring a creative workforce, using corporate accounting software, etc.